Divide and conquer - Capra, Frank; Capra, Frank ([New York] : Army Service Forces, 1999)
Divide and Conquer recounts the successive defeats of Denmark, Norway, Holland, Belgium and France by the seemingly invincible German Army, as seen in dramatic footage from both sides of the battle. The Battle of Britain uses exclusive Army footage and captured Nazi film to portray the indomitable spirit of the heroic Londoners during the Blitz by the Luftwaffe, and to outline Adolf Hitler's six-point plan to annihilate England.'--Publisher
VCD format
Keywords: War films; World War II